(untitled) (Tanzania Medical Journal, 2022)
Background Inappropriate pre-referral care and delays in primary health care facilities contribute to poor patients’ outcomes in secondary and tertiary referral health care facilities. This study was set to determine the proportion, appropriateness and immediate outcome of referrals in paediatrics wards at Bugando Medical Centre (BMC). Methods A cross-sectional study included reffered children aged 1-59 months in BMC paediatrics wards. The minimum required sample size of 287 was determined by the Taro Yamane scientific formula, we excluded self-referral patients and those who misplaced their referral letters. Referral forms were reviewed, detailed history and thorough physical examination were done. Children were reviewed after 48 hours to determine the immediate outcome. Data were analysed using STATA version 15.1. By logistic regression we determined the association between appropriateness of referrals, clinical factors and outcomes and a p-value < 0.05 was considered to be statistically significant. Results Out of 602 admissions 55.1% (332/602) were referrals, and total of 300 children were analysed. Only (6) 2% had appropriately completed referral forms and (10) 3.3% were brought in by an ambulance. A total of 133 (44.3%) referrals were categorized as inappropriate. Deaths occurred in 34 (11.3%) [95% CI 8.2% – 15.5%]. Inappropriate referrals were not associated with increased mortality. Presence of lower chest in drawing (OR: 4.9; 95% CI: 1.7 – 13.8; p=0.003), lower limb swelling (OR: 3.6; 95% CI: 1.3 – 10.2; p=0.013), convulsion (OR: 8.1; 95% CI: 2.2 – 29.9; p=0.008), shock (OR: 9.7 95% CI: 1.8 – 52.6; p=0.008), age >2 years (OR: 5.2; 95% CI: 1.7 – 16.2; p=0.004), and inability breastfeed or drink (OR: 7.3; 95% CI: 2.2 – 23.7; p=0.001) were directly associated with mortality in the referred children. Conclusion and recommendations More than 50% of patients seen are referrals, and 34% of them end up in mortality but inappropriateness of referrals was not directly associated with mortality. The mortality in referred patients is linked to serious illness. Improving the capacity of management of paediatric emergencies in health facilities should go hand in hand with improvement of referral appropriateness in order to improve the overall outcome.